2020
DOI: 10.1007/s11252-020-00950-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple behavioral traits between urban and rural squirrels

Abstract: Recent rapid urbanization has imposed novel challenges to animals. Urban animals alter their behaviors such as increased boldness, exploration, and aggressiveness to cope with anthropogenic disturbance. However, most previous studies were highly biased toward birds and examined a limited number of behavioral traits, often employing species-specific methods. Thus, we still do not fully understand how other taxa behaviorally adjust to urbanization. In this study, we investigated multiple behavioral traits betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 44 publications
6
21
0
Order By: Relevance
“…Reported results of increasing boldness with increasing urbanisation are consistent with the results of previous studies, which suggested that a higher risktaking tendency is adaptive during invasion of novel environments (e.g. 65,81 , but see 82 ). Higher boldness, defined as an individual's reaction to any risky situation, including encounters with predators and humans 17 is thus likely to help coping with the threats and challenges posed by "city life", from traffic and other human disturbances to responses to higher numbers of predators.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Reported results of increasing boldness with increasing urbanisation are consistent with the results of previous studies, which suggested that a higher risktaking tendency is adaptive during invasion of novel environments (e.g. 65,81 , but see 82 ). Higher boldness, defined as an individual's reaction to any risky situation, including encounters with predators and humans 17 is thus likely to help coping with the threats and challenges posed by "city life", from traffic and other human disturbances to responses to higher numbers of predators.…”
Section: Discussionsupporting
confidence: 90%
“…Differential selective pressure in different stages of colonisation might explain why in some cases urban individuals show similar risk-taking to their rural counterparts (e.g. 82,84,88 ). Long-term and population genetics data alongside behavioural assessments are needed to assess if and how such a shift in favoured conditions takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Our results from the trials conducted without playbacks also support our assumption that squirrels in urban areas were habituated to human presence whereas those in less urban areas were not. Similar to most other studies in terrestrial animals (Samia et al, 2015) and in studies specifically in tree squirrels (McCleery, 2009;Engelhardt and Weladji, 2011;Sarno et al, 2015;Uchida et al, 2020), we found that squirrels in urban areas exhibited a shorter FAD and FID, lower probability to climb a tree to escape the human observer, and a shorter latency to resume typical behavior following the trial, although only FID was significantly different. Focusing only our trials without playbacks, our results are similar to Uchida et al (2019) as they suggest that the reduction in FID that we observed in urban squirrels is due to both reduced vigilance and habituation to humans given that we found a lower FAD (vigilance) and FID (habituation) in squirrels in the urban areas.…”
Section: Discussionsupporting
confidence: 89%
“…A study in New York, United States, found that 90% of urban gray squirrels increased their FID when approached by humans that veered off the sidewalk and looked at them, while squirrels from the same population did not increase FID if approaching humans remained on the sidewalk (Bateman and Fleming, 2014). Likewise, urban Eurasian red squirrels demonstrated the ability to assess risk levels of various approaching objects (e.g., humans and conspecific decoys) and modulated their FID accordingly (Uchida et al, 2019(Uchida et al, , 2020. Finally, a study on Australian fur seals (Arctocephalus pusillus doriferus) found that seals modulated their alert response based on vessel type and whether or not vessels conformed with mandated approach distance thresholds-indicating that the seals learned the legal distance ships were able to approach (Speakman et al, 2020).…”
Section: Modulating Behaviormentioning
confidence: 99%